Efektivitas Konseling Kelompok Dengan Teknik Thought Stopping Untuk Mereduksi Kecanduan Judi Koprok - Reni Marisa; Komaruddin Komaruddin; Lena Marianti (Scidacplus, 2023)
The background of this research is that the fathers in Sindang Marga village are very obsessed with the koprok gambling game, that those who do koprok gambling actually do not only fulfill the economy, but they think that by doing this gambling they can improve their standard of living with small capital and get profits. the big ones seem to have to work hard. This study examines the